Paradigma Dakwah Islam Kyai dalam Kancah Politik Kekuasaan Pasca Kemerdekaan di Indonesia - Rojabi Azharghany; Abdul Adim; Hae Ruli Rusdi (UIN Antasari Banjarmasin, 2022)
This paper aims to review the politics of Islam kiai affiliated to the nahdlatul ulama (NU) religious organization by explaining the historical social arguments and strategies pursued by this religious elite to continue to play a role in the lives of Muslims. Kiai can continue to exist with his honorable position, facing political dynamics in the current modernization of Muslim life. This study method uses the madzhab of social history as a research method to look at the social background in the political history of Islam kiai as well as contain critical aspects to analyze the political dynamics of Islam kiai. Data analysis by reconstructing socio-political events involving traditionalist kiai on the Indonesian political stage from the time of independence until the 2019 election. The results showed that the Islamic politics promoted by the Kiai were based on Islamic teachings about social concerns such as maslahah mursalah (the concept of putting goodness first) and kulliatul khoms (the concept of the five basic human rights) which were sparked in the formulation of the concept of the kiai movement, namely mabadi' khoiru ummah (pioneering towards the best people) and syuun ijtimaiyah (social concern).